NUTRITIONAL PROFILE OF POSITIVE HIV PATIENTS IN APUCARANA, BRAZIL - Gomes, Tatiane Bordini (2016)
Knowledge on the nutritional profile of HIV patients is a first step towards an adequate nutrition and successful treatment to guarantee an improvement in life quality. Current analysis assesses the nutritional profile of patients with HIV in Apucarana PR Brazil. Data on weight, height, body mass index, circumference of hips, circumference of arms, tricipital skinfold thickness and muscular circumference of the arm were collected. A questionnaire on food frequency and a questionnaire on the disease were also applied. Results showed a change in the nutritional profile of the patients, revealing that 45.5% were overweight, followed by eutrophic subjects. Changes are related to anti-retroviral drugs which redistribute body weight as a side effect.